Association of Endocrine Therapy With Overall Survival in Women With Small, Hormone Receptor–Positive, ERBB2-Negative Breast Cancer - Ma, Sung Jun (JAMA Netw Open, 2020)
This cohort study examines the association of overall survival with endocrine therapy to treat hormone receptor–positive, ERBB2-negative breast cancer.